PENERAPAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN INSTALASI TENAGA LISTRIK KELAS XI TITL 1 DI SMK NEGERI 5 MAKASSAR - Aldiansyah Nur Alam; Muh. Yusuf Mappeasse; Darmawang (UNM Journal of Technology and Vocational, 2023)
This research aims to determine the increase in learning outcomes and student activity and interest in the Electrical Power Installation (ITL) subject through the Project Based Learning (PjBL) learning model for class XI TITL-1 at SMK Negeri 5 Makassar. This research is classroom action research with a model developed by Kemmis and Mc Taggart. The subjects of this research were students in class XI TITL 1, even semester, 2021/2021 academic year, with a total of 29 students. This research consisted of two cycles with two meetings in each cycle. Data collection techniques in this research used observation, learning outcomes tests, and documentation. The data analysis technique used is qualitative descriptive analysis.The results of the research show that the application of the Project Based Learning (PBL) learning model in ITL subjects can improve learning outcomes, interest and activeness of class XI TITL 1 students at SMK Negeri 5 Makassar. This can be seen based on the results of observations at each meeting, in cycle I it was 73.54%. In cycle II it increased to 81.3%. The average student learning activity per cycle increased from 83% in cycle I to 90.17% in cycle II, where during the Pre-Test the percentage of interest based on the questionnaire given to students was only 67.45% and activeness was only 66.5%. %. Based on the results of the post test and practice in cycle I and cycle II, the student learning outcomes in cycle I showed a class average of 76.38 and 92.75.